Desain Sendok Salad Kayu Menggunakan Metode ATUMICS - Suryadiraji, Aksal; Taruna, Ari Plega (Fakultas Desain Universitas Komputer Indonesia, 2022)
The history of the development of human life cannot be separated from culture and literary works that contain the value of life as well as science to this day. One of the cultural products is tableware. As omnivores, humans innovate and adapt in fulfilling their life needs, especially regarding primary needs. In the primary need for food, spoons are everyday tools used by humans. In the historical development of human civilization, spoons have evolved and developed variations in terms of function, one of which is a salad spoon. A salad spoon is a tool made especially in the process of moving and/or consuming salads, and is very popular in the Scandinavian region. This presentation about the design of the salad spoon aims to determine the development of the salad spoon design from the beginning of its invention to the future. The ATUMICS method was used to analyze and explore more detailed information about salad spoons.